2011
DOI: 10.3168/jds.2010-4015
|View full text |Cite
|
Sign up to set email alerts
|

Variation in residual feed intake in Holstein-Friesian dairy heifers in southern Australia

Abstract: Feed conversion efficiency of dairy cattle is an important component of the profitability of dairying, given that the cost of feed accounts for much of total farm expenses. Residual feed intake (RFI) is a useful measure of feed conversion efficiency, as it can be used to compare individuals with the same or differing levels of production during the period of measurement. If genetic variation exists in RFI among dairy cattle, selection for lower RFI could improve profitability. In this experiment, RFI was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
3

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 44 publications
7
110
3
Order By: Relevance
“…Williams et al (2011) found that Holstein-Friesian dairy heifers with the 10% lowest RFI ate 1.7 kg less DM each day than the 10% highest RFI ones to achieve the same rate of growth. Similarly, our results showed that the more efficient dairy cattle (the low RFI group) ate 1.59 kg less DM each day and produced nearly equal 4% FCM.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al (2011) found that Holstein-Friesian dairy heifers with the 10% lowest RFI ate 1.7 kg less DM each day than the 10% highest RFI ones to achieve the same rate of growth. Similarly, our results showed that the more efficient dairy cattle (the low RFI group) ate 1.59 kg less DM each day and produced nearly equal 4% FCM.…”
Section: Discussionmentioning
confidence: 99%
“…Residual feed intake (RFI), sometimes referred to as net feed intake, is the difference between actual and predicted DMI (Koch et al, 1963;Williams et al, 2011;Berry and Crowley, 2013). RFI is calculated as the residual from a regression model of DMI on various energy sinks, such as milk production and live weight (for maintenance requirements).…”
Section: Definitions Of Feed Efficiencymentioning
confidence: 99%
“…A recent Australian and New Zealand project measured RFI in around 2000 growing Holstein heifers and genotyped them with 625 000 SNP (Pryce et al, 2012a;Waghorn et al, 2012;Williams et al, 2011). A prediction equation for growing heifer RFI was derived in this data set.…”
Section: Genomic Selection For Feed Efficiency In Growing Heifersmentioning
confidence: 99%
“…Negative values are indicative of cows that eat less than predicted for their level of milk production. Developing a genomic prediction tool for this trait has been the focus of a large collaboration between researchers in Australia and New Zealand, initially involving measurement of feed-intake phenotypes of~1000 Holstein-Friesian heifers of~6 months of age in each country (Williams et al 2011b). The accuracy of trait prediction using this population was~0.4 , which is equivalent to a reliability of 0.16.…”
Section: Genomic Selectionmentioning
confidence: 99%
“…An example of the implementation of genomic selection within the Australian Holstein-Friesian population is selection for improved feed conversion efficiency (Williams et al 2011b). The trait used by Williams et al (2011b) was residual feed intake (RFI), which is the difference between actual and predicted feed intake. Negative values are indicative of cows that eat less than predicted for their level of milk production.…”
Section: Genomic Selectionmentioning
confidence: 99%